1992
DOI: 10.1259/0007-1285-65-778-895
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hydration status on body composition as measured by dual energy X-ray absorptiometry in normal volunteers and patients on haemodialysis

Abstract: To evaluate the influence of hydration status on the estimation of body composition using dual-energy X-ray absorptiometry (DXA), six normal volunteers and seven patients on maintenance haemodialysis were investigated using two different DXA machines (Lunar DPX, Hologic QDR 1000/W). Normal volunteers were studied (Hologic QDR 1000/W) before and 1 h after ingestion of breakfast, lunch and dinner (drinking various amounts of liquids at each meal, 0.5-2.4 kg). Whereas bone mineral content and body fat mass did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
75
1
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(84 citation statements)
references
References 5 publications
6
75
1
1
Order By: Relevance
“…This type of intervention related to hydration status (hypo-and hyper-hydration) has only been analysed previously in non-athletic groups using 24h fluid restriction or dialysis (Going et al, 1993;Horber, Thomi, Casez, Fonteille, & Jaeger, 1992). In the present study, baseline measures (initial body mass, initial hydration status, sum of skinfolds, impedance and body composition), and environmental conditions were all consistent and demonstrated that under these experimentally controlled conditions estimates of body composition are reliable.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This type of intervention related to hydration status (hypo-and hyper-hydration) has only been analysed previously in non-athletic groups using 24h fluid restriction or dialysis (Going et al, 1993;Horber, Thomi, Casez, Fonteille, & Jaeger, 1992). In the present study, baseline measures (initial body mass, initial hydration status, sum of skinfolds, impedance and body composition), and environmental conditions were all consistent and demonstrated that under these experimentally controlled conditions estimates of body composition are reliable.…”
Section: Discussionsupporting
confidence: 70%
“…Studies on the influence of daily activities, meal ingestion, and acute exercise on body composition estimates have already been performed in healthy controls (Horber, Thomi, Casez, Fonteille, & Jaeger, 1992) and more recently on athletes (Nana, Slater, Hopkins, & Burke, 2013;Nana, Slater, Hopkins, & Burke, 2011). Furthermore, previous work has not compared DXA estimates with skinfolds/impedance analysis outcomes following an acute fluid deficit.…”
Section: Introductionmentioning
confidence: 99%
“…Variations around this assumed constant can result in error. Despite this limitation, the error in %BF associated with hydration seems to be small (Horber et al, 1992). DXA is also limited in how it determines the density of tissue directly over bone.…”
Section: Discussionmentioning
confidence: 99%
“…DXA (Hologic Discovery A, Waltham, MA) was used to assess tissue composition of the limbs using a 3-compartment model sensitive to changes in fluid retention. 39,40 Measurements were converted into volume using known densities of adipose tissue (0.9167 g/mL ≈ 0.92 g/cm 3 ), lean tissue (1.0615 g/mL ≈ 1.06 g/cm 3 ), and bone (3.15 g/cm 3 ), a method shown to correlate very highly (r = .996, P < .0001) with total arm volume measurement by plethysmography. 41 Absolute values of the total volume for the affected arm as well as the volume difference between the affected and non-affected arms were reported.…”
Section: Outcome Measuresmentioning
confidence: 99%